Mecanismos del estado para evitar se le declare responsable internacionalmente ante la Corte Interamericana de Derechos Humanos - Piña García, Denny Eryck Nilson (2014)
The State’s international responsibility is the main focus of this research, it precisely analyses the mechanisms by which this can be avoided in front of an International Tribunal, specifically the Inter-American Court of Human Rights. Taking into consideration for this, the existence of a standard legal jurisprudence that not only protects and guarantees human rights, but also establishes parameters for compliance regarding the obligations of States. This allows us to state that the fulfillment of their obligations as part of the Regional Human Rights Protection System is the mechanism that enables States to avoid international responsibility and subsequent reparation costs. Therefore, this work has served to determine the obligations to investigate and provide access to repair as mechanisms that prevent the declaration of international responsibility towards the State. Using the scientific research method, through inductive and deductive, hermeneutic-legal and analytic-synthetic methods, which have allowed analyze and contrast the study material containing the sample population of this research, allowing the achievement of the objectives arriving of the results. Furthermore, the research has allowed through the results, which is the suitable set standard of the studied obligations to avoid the declaration of international responsibility by an International Tribunal, taking into consideration that internationally wrongful acts could exists but its compensation within the States avoids considering the legal institution of international responsibility as solution to it. To reach to this issue this paper develops the relevant theoretical framework that goes from international law to human rights. Indeed, it has been established in the investigation that the interamerican standard has a set of necessary measures whose compliance and implementation are the mechanism to prevent the declaration of international responsibility, and that this is a legal category of protection of the individual under the Inter-American System protection of Human Rights does not operate. Finally, after verifying the results with the theoretical framework, through a logical process of contrasting, have led to the conclusions of this study, among which stands out precisely that compliance with the standard established by the jurisprudence of the Inter-American Human Rights Court, provides the mechanism to avoid responsibility before this Court. In addition, that allows us to make recommendations that could apply to Perú, as a member state of the alluded protection system